The CRISPR/Cas Adaptive Immune System of Pseudomonas aeruginosa Mediates Resistance to Naturally Occurring and Engineered Phages - Cady, Kyle C. (American Society for Microbiology, 2012)
Here we report the isolation of 6 temperate bacteriophages (phages) that are prevented from replicating within the laboratory strain Pseudomonas aeruginosa PA14 by the endogenous CRISPR/Cas system of this microbe. These phages are only the second identified group of naturally occurring phages demonstrated to be blocked for replication by a nonengineered CRISPR/Cas system, and our results provide the first evidence that the P. aeruginosa type I-F CRISPR/Cas system can function in phage resistance. Previous studies have highlighted the importance of the protospacer adjacent motif (PAM) and a proximal 8-nucleotide seed sequence in mediating CRISPR/Cas-based immunity. Through engineering of a protospacer region of phage DMS3 to make it a target of resistance by the CRISPR/Cas system and screening for mutants that escape CRISPR/Cas-mediated resistance, we show that nucleotides within the PAM and seed sequence and across the non-seed-sequence regions are critical for the functioning of this CRISPR/Cas system. We also demonstrate that P. aeruginosa can acquire spacer content in response to lytic phage challenge, illustrating the adaptive nature of this CRISPR/Cas system. Finally, we demonstrate that the P. aeruginosa CRISPR/Cas system mediates a gradient of resistance to a phage based on the level of complementarity between CRISPR spacer RNA and phage protospacer target. This work introduces a new in vivo system to study CRISPR/Cas-mediated resistance and an additional set of tools for the elucidation of CRISPR/Cas function.